Relationship between platelet-to-lymphocyte ratio and fractional flow reserve in left anterior descending artery with intermediate stenosis - Asoglu, Ramazan; Afsin, Abdulmecit; Atici, Adem; Asoglu, Emin (Annals of Medical Research, 2021)
Aim: Platelet-to-lymphocyte ratio has been used as a determinant factor for coronary artery disease. Since platelet activation is central to the initiation of atherosclerosis, our goal was to evaluate the relationship between platelet-to-lymphocyte ratio and fractional flow reserve (FFR) values in the left anterior descending artery (LAD) with intermediate coronary stenosis.Material and Methods: The present report encompassed 173 subjects having stable angina pectoris. These subjects were categorized into 2 groups: 91 subjects with a FFR less than or equal to 0.80 and 82 patients with a FFR greater than 0.80. The platelet-to-lymphocyte ratio of each subject was determined from the complete blood count. The two groups were evaluated for differences using a Student’s unpaired t-test. A p-value of 0.05 was considered statistically significant.Results: The average platelet-to-lymphocyte ratio value of subjects with a FFR less than or equal to 0.80 were significantly higher than those with a FFR greater than 0.80 ((115.5±38.0) vs. (103.8±38.9), p=0.04). The correlation between platelet-to-lymphocyte ratio with stenosis degree was significant (r= 0.22, p= 0.003).Conclusion: Platelet-to-lymphocyte ratio was associated with a FFR measurement of equal or less than to 0.80 in subjects with stable angina pectoris.